An ionic liquid‐enhanced soy protein adhesive with high bonding strength and antibacterial activity. Issue 16 (16th February 2023) - Zhang, Hongwei; Zhang, Yanchao; Gao, Haixiang; Zhou, Wenfeng
Abstract: Traditional formaldehyde resin adhesives can release harmful substances, which endanger human health and contribute to environmental pollution. The development of alternative high‐performance, environmentally benign adhesives is therefore of great importance. In this study, we evaluate the effect of several additives on the properties and performance of soy protein isolate adhesive, a bio‐based adhesive. Triglycidyl isocyanurate, a chemically cross‐linker, 1, 3‐dimethyl imidazolium hexafluorophosphate ([MMIM]PF6 ), a crystalline ionic compound, and borax, which is covalently reactive with hydroxyl groups, were added to soy protein isolate to build a dense network structure. The wet shear strength of the adhesive prepared with all additives was 109% greater than that of the unmodified soy protein isolate adhesive (1.34 vs. 0.64 MPa). This improvement is due to the synergistic enhancement of the bonding strength through covalent cross‐linking and hydrogen‐bonding interactions. In addition, the anti‐fungal properties of the adhesive were significantly improved through the use of chemical additives. This work provides a new approach for the preparation of high‐performance, antimicrobial, bio‐based adhesives, which will be beneficial in the development of greener alternatives to commonplace chemicals. Abstract : We report a crystalline imidazole derivative [MMIm]PF6 ‐reinforced soy protein isolate adhesive for use as a high strength antibacterial bio‐based adhesive.